Nanostructure and reactivity of carbon particles from co-pyrolysis of biodiesel surrogate methyl octanoate blended with n-butanol. Issue 5 (4th May 2018) - Liu, Dong; Wang, Wei; Ying, Yaoyao; Luo, Minye
ABSTRACT: This paper presents nanostructure and reactivity of carbon particles (soot) from co-pyrolysis of biodiesel surrogate methyl octanoate blended with n -butanol at temperatures from 1023 K to 1223 K in a quartz tube flow reactor, as n -butanol concentration increases from 0 to 50% (mole fraction) in the mixed fuels. The soot structure was characterized by low and high resolution transmission electron spectroscopy (LRTEM and HRTEM) and X-ray diffraction (XRD). The soot reactivity was investigated by thermogravimetric analyzer (TGA). When the pyrolysis temperature increased, as well as the rise of n -butanol addition, soot presented the higher degree of graphitization with the larger fringe length and lower fringe tortuosity. TGA results revealed that the higher amount addition of n -butanol can induce the formations of less reactive soot, and soot yielded at lower temperatures was more reactive than that at high temperatures. In addition, the high correlations between soot reactivity with its nanostructure were given in details.